The EVALUASI EFEKTIVITAS PROGRAM PENDAMPINGAN UMKM BINAAN BANK INDONESIA DALAM PEMANFAATAN APLIKASI SIAPIK DI JAWA TENGAH: (Studi Kasus UMKM Klaster Bawang Merah Desa Pasir Kecamatan Mijen Kabupaten Demak) - Vikri Mustaqim (Universitas Muhammadiyah Surakarta, 2025)
This research aims to evaluate the effectiveness of Bank Indonesia's mentoring program in utilizing the SIAPIK (Sistem Informasi Aplikasi Pencatatan Informasi Keuangan) application to improve financial management of SMEs in Central Java. The research focuses on SMEs in the Red Onion Cluster in Pasir Village, Mijen District, Demak Regency. The methodology used in this research is qualitative with a case study approach. Data were collected through in-depth interviews with SME owners, direct observation of the use of the SIAPIK application, and analysis of related documents. The results of this research show that the use of the SIAPIK application has a positive impact on the ability of SMEs to prepare more accurate and structured financial reports. Most of the SMEs participating in this program reported improvements in financial management and operational efficiency. Although there were some challenges in the initial adaptation to new technology, intensive training and mentoring helped SMEs overcome these challenges. These findings indicate that the SIAPIK application can be an effective tool in supporting the growth and sustainability of SMEs in Indonesia.